Nickel-iron-based MOFs heterostructure catalyst as well as synthesis method and application thereof
By introducing Fe elements to nickel-based MOFs to construct heterostructure, the problem of slow kinetics and high overpotential of the anode oxygen evolution reaction during electrolytic hydrocarbon production is solved, and high efficiency and low energy consumption of hydrogen generation is achieved, which is better than traditional precious metal catalysts.
Patent Information
- Application Number
- CN202510042804.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-10
- Publication Date
- 2025-04-25
AI Technical Summary
The kinetics of the anode oxygen evolution reaction in the electrolytic water hydrogen production process of existing electrocatalysts are slow and overpotential, resulting in increased energy consumption and increased costs, limiting the development of the hydrogen energy industry.
Design and synthesize the heterostructure catalyst of nickel-iron-based MOFs. By introducing Fe elements on the basis of nickel-based MOFs to construct the heterostructure, the stability and conductivity of the catalyst are improved, thereby improving the catalytic activity.
It has achieved improved efficiency of electrolyzed hydrogen production at low overpotentials, which is better than traditional precious metal catalysts Ir/C and RuO2, and has good stability and application potential.
Smart Images

Figure CN119877027A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of electrocatalysts, and in particular to a nickel-iron-based MOFs heterostructure catalyst, a synthesis method thereof and applications thereof. Background Art
[0002] The technology of hydrogen production by alkaline water electrolysis is low in cost, relatively high in industrialization degree, easy to achieve large-scale application, and the technology has been commercialized. In the process of water electrolysis, the cathode hydrogen evolution reaction and the anode oxygen evolution reaction are two core electrochemical reactions. The efficiency of these two reactions directly affects the overall efficiency and cost of hydrogen production by water electrolysis. The anode oxygen evolution reaction is a typical four-electron reaction, which means that four electrons need to be transferred to generate an oxygen molecule during the reaction. This multi-electron transfer process is usually accompanied by complex intermediate steps, resulting in sluggish reaction kinetics, that is, a slow reaction rate. In addition, due to the high energy state of these intermediate steps, the oxygen evolution reaction usually requires a higher overpotential to drive, which increases the energy consumption of hydrogen production by water electrolysis, increases the difficulty and cost of the hydrogen production process, and greatly limits the development and promotion of the hydrogen energy industry. Therefore, OER has also been studied more deeply.
[0003] In view of the problems of sluggish kinetics and high overpotential in OER reaction, designing and synthesizing efficient OER catalysts is indeed one of the effective ways to improve the energy efficiency of hydrogen production by water electrolysis. 2 Although and Ir / C are the most effective OER electrocatalysts, their high prices, scarce resources and scarce energy storage limit their large-scale applications. Therefore, transition metal elements such as nickel, cobalt, and iron are widely studied and applied to the development of new electrocatalysts due to their relatively low cost and abundant resources. Among them, nickel has been widely studied in the field of electrochemistry due to its low price and rich energy storage. Nickel-based Metal Organic Frameworks, Ni MOFs, exhibit high performance, high stability and easy preparation in electrocatalytic water splitting, which makes them a research field that has attracted much attention. Summary of the invention
[0004] Based on this, the purpose of the present invention is to provide a nickel-iron-based MOFs heterostructure catalyst, a synthesis method and an application thereof, by synthesizing a stable Ni MOFs material and introducing the Fe element on this basis to construct a heterostructure, thereby solving the stability and conductivity problems of MOFs materials in the field of electrocatalytic water decomposition and further improving their catalytic activity.
[0005] The present invention adopts the following technical solution:
[0006] A method for synthesizing a nickel-iron-based MOFs heterostructure catalyst comprises the following steps:
[0007] S1. Preparation of Ni BDC: Measure N,N-dimethylformamide in a measuring cylinder and pour it into a beaker. Use a balance to weigh terephthalic acid and add it to the beaker containing N,N-dimethylformamide for ultrasonic dissolution. After the terephthalic acid is completely dissolved, add deionized water and ethanol, and then weigh NiCl 2 6H 2 O is added to the beaker and sonicated until completely dissolved;
[0008] Stir with a disposable rubber-tipped dropper to mix evenly, then pour into the polytetrafluoroethylene liner of a 50 mL stainless steel reactor and add the cleaned nickel foam;
[0009] Put the inner container into the reactor, tighten the lid, and put it into the air drying oven for reaction;
[0010] After the reaction is completed, the reactor is taken out and allowed to cool naturally to room temperature, the inner tank is taken out, the reaction product is taken out and ultrasonically treated with water and ethanol respectively, and then dried in a blast drying oven to obtain a Ni BDC sample, and the obtained sample is marked and packaged;
[0011] S2. Synthesis of Ni BDC@Fe BDC: Measure N,N-dimethylformamide in a measuring cylinder and pour it into a beaker. Use a balance to weigh FeCl 3 6H 2 Add O into the beaker, stir thoroughly with a rubber-tipped dropper to mix evenly, and then pour into the reactor liner;
[0012] Take out Ni BDC and put it into a 50mL inner liner and keep a record, while ensuring that Ni BDC is in full contact with the solution. Put the inner liner into the reactor, tighten the lid, and put it into the air drying oven for reaction;
[0013] After the reaction is completed, the reactor is taken out and allowed to cool naturally to room temperature. The inner tank is taken out, the reaction product is taken out and washed with water and ethanol respectively, and then placed in a forced air drying oven for drying. After drying, the marked package is taken out to obtain a nickel-iron-based MOFs heterostructure catalyst.
[0014] A further improvement to the above technical solution is that in step S1, the ratio of N,N-dimethylformamide to terephthalic acid is 30 mL-32 mL: 240 mg-250 mg.
[0015] A further improvement to the above technical solution is that in step S1, the ratio of the N,N-dimethylformamide, deionized water and ethanol mixed solution is 30mL-32mL: 2mL-3mL.
[0016] A further improvement to the above technical solution is that in step S1, the NiCl 2 6H 2 The ratio of O to terephthalic acid is 350mg-360mg:240mg-250mg.
[0017] A further improvement to the above technical solution is that in step S1, the inner container is placed in a reaction kettle, the lid is tightened, and the reaction is placed in a forced air drying oven, wherein the reaction temperature is 100°C-150°C and the reaction time is 12h-24h.
[0018] A further improvement to the above technical solution is that in step S1, the NiBDC sample is dried in a blast drying oven, wherein the drying temperature is 60°C-80°C.
[0019] A further improvement to the above technical solution is that in step S2, the inner container is placed in a reaction kettle, the lid is tightened, and the reaction is placed in a forced air drying oven, wherein the reaction temperature is 100°C-150°C and the reaction time is 12h-24h.
[0020] A further improvement to the above technical solution is that in step S2, FeCl is weighed using a balance. 3 6H 2 The mass of O is 20mg-100mg.
[0021] A nickel-iron based MOFs heterogeneous structure catalyst is prepared by using the synthesis method.
[0022] An application of a nickel-iron-based MOFs heterostructure catalyst, wherein the nickel-iron-based MOFs heterostructure catalyst prepared by the synthesis method is applied to electrocatalytic water splitting.
[0023] The beneficial effects of the present invention are:
[0024] The present invention uses terephthalic acid as a ligand to construct a nickel-iron-based MOFs heterostructure catalyst on the basis of nickel-based MOFs. As the amount of iron added increases, the amount of heterostructure increases accordingly, and the performance gradually improves; when the ferric chloride content reaches 80 mg, the amount of heterostructure almost reaches the maximum. If the iron content is further increased, the excess Fe BDC will detach from the Ni BDC surface. Electrochemical test data found that Ni BDC@Fe BDC at 50 mA cm -2 The overpotential under the condition is only 251mV, and the Tafel slope is 24.8mV·dec -1 , better than precious metals Ir / C and RuO 2 and Ni BDC, while achieving good stability and showing excellent application potential. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 XRD patterns of Ni BDC@Fe BDC with different iron contents of the nickel-iron-based MOFs heterostructure catalyst of the present invention;
[0026] Figure 2 The morphology observation diagram of Ni BDC and Ni BDC@Fe BDC-80 of the nickel-iron-based MOFs heterostructure catalyst of the present invention is shown in FIG. Figure 2 (a) is the SEM image of Ni BDC. Figure 2 (b) is the SEM image of Ni BDC@Fe BDC-80. Figure 2 (cd) are TEM bright-field and dark-field images of NiBDC@Fe BDC-80. Figure 2 (eh) is the element mapping of Ni BDC@Fe BDC-80 (e: Ni; f: Fe; g: C; h: O; i: Mix);
[0027] Figure 3 The SEM images of Ni BDC@Fe BDC of the nickel-iron-based MOFs heterostructure catalyst of the present invention at different iron contents;
[0028] Figure 4 Schematic diagram of the electrochemical test results of the nickel-iron-based MOFs heterostructure catalyst of the present invention, wherein Figure 4 (a) Ni BDC, Ni BDC@Fe BDC, Ir / C, RuO 2 , LSV curve of Ni foam, Figure 4 (b) Ni BDC, Ni BDC@Fe BDC, Ir / C, RuO 2 , Tafel diagram of Ni foam, Figure 4 (c) Ni BDC, Ni BDC@Fe BDC, Ir / C, RuO 2 , Nifoam's electrochemical impedance test chart, Figure 4 (d) is the double layer capacitance C dl value;
[0029] Figure 5 Ni BDC, Ni BDC@Fe BDC, Ir / C, RuO 2 , LSV curve of Ni foam;
[0030] Figure 6 is the double-layer capacitance C of Ni BDC@Fe BDC at different iron contents of the nickel-iron-based MOFs heterostructure catalyst of the present invention dlValue diagram;
[0031] Figure 7 The EIS graphs of Ni BDC@Fe BDC of the nickel-iron-based MOFs heterostructure catalyst of the present invention at different iron contents;
[0032] Figure 8 The Faraday efficiency and chronopotentiometry analysis diagram of the nickel-iron-based MOFs heterostructure catalyst of the present invention are shown in FIG. Figure 8 (a) is a comparison diagram of Tafel and overpotential of Ni BDC@FeBDC and other nickel-based catalysts. Figure 8 (b) is the Faraday efficiency diagram measured by the water displacement method. Figure 8 (c) Chronopotentiometry analysis of Ni BDC@Fe BDC. DETAILED DESCRIPTION
[0033] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0034] In the description of the present invention, it should be noted that the terms "vertical direction", "up", "down", "horizontal", etc., indicating the orientation or positional relationship, are based on the orientation or positional relationship shown in the drawings, and are only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as limiting the present invention. In addition, "first", "second", "third", and "fourth" are only used for descriptive purposes and cannot be understood as indicating or implying relative importance.
[0035] In the description of the present invention, it is also necessary to explain that, unless otherwise clearly specified and limited, the terms "set", "install", "connect", and "connect" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection, it can be a mechanical connection, it can be an electrical connection, it can be a direct connection, it can be connected through an intermediate medium, and it can be the internal communication of two components. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.
[0036] The present invention relates to a method for synthesizing a nickel-iron-based MOFs heterostructure catalyst, comprising the following steps:
[0037] Preparation of Ni BDC: Measure 31.5 mL of N,N-dimethylformamide (DMF) in a measuring cylinder and pour it into a beaker. Use a balance to weigh 249.2 mg of BDC and add it to the beaker containing DMF for ultrasonic dissolution. After BDC is completely dissolved, add 2.25 mL of deionized water and ethanol, and then weigh 356.6 mg of NiCl 2 6H 2 O is added to a beaker and ultrasonicated until completely dissolved. Stir with a disposable rubber-tipped dropper to mix evenly, then pour into the polytetrafluoroethylene liner of a 50mL stainless steel reactor and put in the cleaned nickel foam. Put the liner into the reactor, tighten the lid, and put it in a blast drying oven for reaction at 100°C for 12 hours. After the reaction is completed, take out the reactor and let it cool naturally to room temperature, take out the liner, take out the reaction product, ultrasonically treat it with water and ethanol respectively, and then dry it in a blast drying oven at 60°C to obtain a Ni BDC sample, and mark and package the prepared sample.
[0038] Synthesis of Ni BDC@Fe BDC: Pour DMF into a measuring cylinder and pour into a beaker. Use a balance to weigh 20, 40, 60, 80, and 100 mg of FeCl 3 6H 2 O is added to the beaker, stirred thoroughly with a rubber-tipped dropper to mix evenly, and then poured into the reactor liner. Take out Ni BDC and put it into a 50mL liner and keep a record, while ensuring that Ni BDC is in full contact with the solution. Put the liner into the reactor, tighten the lid, and place it in a forced air drying oven for reaction at 100°C for 12 hours. After the reaction is completed, take out the reactor and let it cool naturally to room temperature, take out the liner, take out the reaction product, wash it with water and ethanol respectively, and then put it in a forced air drying oven for drying. After drying, remove the marked package to obtain a nickel-iron-based MOFs heterostructure catalyst. Mix Ni BDC with FeCl 3 6H 2 O reaction was named Ni BDC@Fe BDC, in which 20 mg of FeCl 3 6H 2 O is named Ni BDC@Fe BDC-20, and so on, they are named Ni BDC@Fe BDC-40, Ni BDC@Fe BDC-60, Ni BDC@Fe BDC-80, and NiBDC@Fe BDC-100 respectively.
[0039] X-ray diffraction was used to analyze the physical phases of Ni BDC@Fe BDC-20, Ni BDC@Fe BDC-40, Ni BDC@Fe BDC-60, Ni BDC@Fe BDC-80 and Ni BDC@Fe BDC-100. The morphology and structural characteristics of the samples were determined by scanning electron microscopy and transmission electron microscopy. The element distribution was confirmed by energy spectrum analyzer. The results are shown below:
[0040] like Figure 1 As shown in the figure, the XRD spectra of Ni BDC@Fe BDC with different iron contents were measured. The XRD analysis results show that the material was successfully synthesized. Ni BDC has an obvious characteristic peak at about 2θ=8.5. When iron ions are added to Ni BDC to synthesize Ni BDC@Fe BDC, by comparing the XRD spectra of the two, it can be found that part of the characteristic peak in the XRD spectrum of Ni BDC@Fe BDC is completely consistent with the peak position of Ni BDC, but a new diffraction peak appears at about 2θ=9.2. The new diffraction peak is the characteristic peak of FeBDC, indicating that Ni BDC@Fe BDC is a composite of Ni BDC and Fe BDC. And with the increase of iron content, the peak intensity of FeBDC continues to increase. When the iron content is 80mg, the two peaks gradually flatten out. When the iron content is 100mg, the characteristic peak of Ni BDC becomes weaker, and the obtained material is closer to Fe BDC.
[0041] like Figure 2 As shown in the figure, the morphology observation diagram of Ni BDC and Ni BDC@Fe BDC-80 was observed by scanning electron microscope. Figure 2 As shown in (a), the prepared Ni BDC has an obvious nanosheet structure. Figure 2 (b) It can also be found that the prepared Ni BDC@Fe BDC-80 has many granular structures attached to the original nanosheet structure, further proving the successful composite of Ni BDC and Fe BDC. NiBDC@Fe BDC-80 was observed using a transmission electron microscope, and the results are as follows: Figure 2 As shown in (cd), the transmittance in some areas is poor, which may be because the electrons are scattered or absorbed more in these areas, resulting in a decrease in the number of transmitted electrons. Figure 2 (eh) is the element mapping diagram of Ni BDC@Fe BDC-80. The element distribution also shows that the area with poor transmittance is due to the fact that the Fe BDC particles are more concentrated in the area where Ni BDC is more distributed, and the electron density is higher in this area.
[0042] like Figure 3The following are SEM images of Ni BDC@Fe BDC with different iron contents. In order to better observe the changes of iron content on the material morphology, the morphology of Ni BDC@Fe BDC with iron contents of 20, 40, 60, and 100 mg was also observed using a scanning electron microscope. Figure 3 (ac) It can be seen that when the iron content is 20mg and 40mg, the granular Fe BDC is less distributed on the original structure. When the iron content is 60mg, although a lot of Fe BDC has been attached, there are still some gaps in the original structure. Figure 2 (b) and Figure 3 (d) The Ni BDC is basically covered with Fe BDC particles, but in the sample with an iron content of 100 mg, the FeBDC particles are enriched in spherical shapes on the surface, which may cause shedding.
[0043] like Figure 4 As shown, it is a schematic diagram of the electrochemical test results of the present invention, wherein Figure 4 (a) Ni BDC, Ni BDC@FeBDC, Ir / C, RuO 2 , LSV curve of Ni foam, Figure 4 (b) Ni BDC, Ni BDC@Fe BDC, Ir / C, RuO 2 、Tafel diagram of Nifoam, Figure 4 (c) Ni BDC, Ni BDC@Fe BDC, Ir / C, RuO 2 , electrochemical impedance test diagram of Ni foam, Figure 4 (d) is the double layer capacitance C dl Schematic diagram of the value; at room temperature, the OER performance of the sample was evaluated in 1M KOH solution using a standard three-electrode system. The test results are shown in Figure 4 As shown in (ad), by comparing the LSV curves, Tafel slopes, EIS graphs, and double-layer capacitances of the samples, it can be concluded that the electrochemical performance of Ni BDC@Fe BDC-80 is significantly better than that of NiBDC and commercial precious metal catalysts Ir / C and RuO 2 .
[0044] like Figure 5 The LSV curves at different iron contents are shown in Figure 2. The OER performance is demonstrated by the linear voltammetry curve. The current density is 50 mA cm -2The oxygen evolution performance of the catalyst is judged by the corresponding overpotential. The smaller the corresponding potential, the better the oxygen evolution reaction performance of the material. This paper systematically discusses the effect of different iron content ratios on the oxygen evolution performance of composite MOFs. In order to obtain the optimal conditions, the LSV curves of a series of synthesized samples were measured. Figure 5 It can be seen that the LSV curves of Ni BDC@Fe BDC-80 and Ni BDC@Fe BDC-100 are the closest. -2 ), its overpotential is lower than that of Ni BDC, Ni BDC@Fe BDC-20, Ni BDC@Fe BDC-40, and Ni BDC@Fe BDC-60. As the iron content increases from 20 mg to 80 mg, its electrochemical performance gradually increases, but when the iron content increases from 80 mg to 100 mg, the increase in iron content has little effect on the electrochemical performance. This corresponds to the previous electron microscopy results. When the iron content is 100 mg, the spherical Fe BDC particles enriched on Ni BDC are accompanied by shedding in the electrochemical test, so it is very close to the LSV curve of NiBDC@Fe BDC-80.
[0045] Ni BDC@Fe BDC with an iron content of 80 mg was selected to react with commercial Ir / C and RuO 2 As can be seen from the figure, the electrocatalytic activity of pure nickel foam is relatively low. -2 When the overpotential of Ir / C is 308mV, RuO 2 The overpotential of Ni BDC is 311mV, the overpotential of Ni BDC is 386mV, and the overpotential of Ni BDC@Fe BDC is only 251mV. At the same current density, the smaller the overpotential, the better the catalyst performance. Therefore, the prepared Ni BDC@Fe BDC has the best catalytic performance. Compared with the monometallic MOFs, the bimetallic MOFs heterostructure material has a higher overpotential than the monometallic MOFs at a current density of 50mA·cm -2 This may be due to the synergistic effect between Fe and Ni ions. At the same time, the heterostructure is constructed, which can adjust the interfacial electronic structure and enhance its catalytic reaction activity.
[0046] like Figure 4 As shown in (b), the Tafel slope of the catalyst can further prove that Ni BDC@Fe BDC has the best catalytic performance. The lower the Tafel slope, the better the catalytic performance of the material in OER. The current density increases rapidly with the increase of overpotential, which can indicate the fast electrocatalytic kinetics of OER. Figure 4 (b) It can be seen that the Tafel slope of Ni BDC is 81.2 mV·dec -1, Ni BDC@Fe BDC is 24.8mV·dec -1 , Ir / C is 63.9mV·dec -1 , RuO2 is 70.5mV·dec -1 NiBDC@Fe BDC has the lowest Tafel slope. Therefore, it can be seen that the synergistic effect brought by Ni and Fe ions and the construction of heterogeneous structures can further improve and enhance the performance of MOFs materials.
[0047] like Figure 6 As shown, the double layer capacitance C of Ni BDC@Fe BDC with different iron contents dl Schematic diagram of the value. The electrocatalytic performance is related to the number of active sites, which can be characterized by the electrochemical specific surface area (ECSA). Electrochemical active area and double layer capacitance C dl The double-layer capacitance of the catalyst is measured by cyclic voltammetry curves at several different scan rates. Figure 6 As shown, the C dl The values are 1.28mF·cm -2 、1.52mF·cm -2 , 1.64mF·cm -2 、1.87mF·cm -2 , 2.06mF·cm -2 and 1.98mF·cm -2 . By calculation, their ECSA values are 32cm 2 、38cm 2 、41cm 2 、46.75cm 2 、51.5cm 2 and 49.5cm 2 The above results indicate that Ni BDC@Fe BDC-80 has a larger electrochemical area, and the contact area between the catalytic active sites and KOH in Ni BDC@Fe BDC-80 is larger than that in Ni BDC.
[0048] To further analyze the electron transfer rate of the catalyst, impedance tests were performed on the materials, such as Figure 7The figure shows the EIS graph of Ni BDC@Fe BDC at different iron contents. The charge transfer resistance of the catalyst during the reaction is represented by the radius of the semicircle in the EIS graph. It is not difficult to see from the figure that the radii of Ni BDC@Fe BDC-80 and Ni BDC@Fe BDC-100 are very close and smaller than Ni BDC@Fe BDC-20, Ni BDC@Fe BDC-40 and Ni BDC@Fe BDC-60. This is consistent with the previous LSV and other test results. Figure 4 As can be seen from the impedance diagram (c), compared with Ni BDC, Ir / C and RuO 2 The arc radius of sample Ni BDC@FeBDC-80 is the smallest, indicating that it has the smallest charge transfer resistance. The higher the electron transfer rate, the best OER catalytic performance, which is also consistent with the performance evaluation obtained from the LSV curve.
[0049] like Figure 8 (a) shows the comparison of Tafel and overpotential of Ni BDC@FeBDC and other nickel-based catalysts. -2 By comparing the overpotential and Tafel slope of the materials to analyze the OER performance of Ni BDC@Fe BDC and other recently reported nickel-based catalysts, it can be seen that the Ni BDC@Fe BDC prepared by the present invention performs better than most nickel-based catalysts; Figure 8 (b) shows the Faraday efficiency diagram measured by the water displacement method. Ni BDC@Fe BDC achieved a Faraday efficiency higher than 95% in catalysis. In order to explore the stability of the catalyst, the present invention conducted a 24-hour stability test on Ni BDC@Fe BDC-80 using chronopotentiometry. The results are shown in FIG. Figure 8 As shown in (c), Ni BDC@FeBDC-80 exhibits good stability.
[0050] The present invention uses terephthalic acid as a ligand to construct a nickel-iron-based MOFs heterostructure catalyst on the basis of nickel-based MOFs. As the amount of iron added increases, the amount of heterostructure increases accordingly, and the performance gradually improves; when the ferric chloride content reaches 80 mg, the amount of heterostructure almost reaches the maximum. If the iron content is further increased, the excess Fe BDC will detach from the Ni BDC surface. Electrochemical test data found that Ni BDC@Fe BDC at 50 mA cm -2 The overpotential under the condition is only 251mV, and the Tafel slope is 24.8mV·dec -1 , better than precious metals Ir / C and RuO 2 and Ni BDC, while achieving good stability and showing excellent application potential.
[0051] The above only expresses the preferred technical solution of the present invention, and its description is relatively specific and detailed, but it cannot be understood as limiting the scope of the invention patent. It should be pointed out that for ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present invention, and the present invention is also intended to include these modifications and modifications.
Claims
1. A method for synthesizing a nickel-iron-based MOFs heterostructure catalyst, characterized in that: The steps include: S1. Preparation of Ni BDC: Measure N,N-dimethylformamide in a measuring cylinder and pour it into a beaker. Use a balance to weigh terephthalic acid and add it to the beaker containing N,N-dimethylformamide for ultrasonic dissolution. After the terephthalic acid is completely dissolved, add deionized water and ethanol, then weigh NiCl2·6H2O and add it to the beaker for ultrasonic dissolution until it is completely dissolved. Stir with a disposable rubber-tipped dropper to mix evenly, then pour into the polytetrafluoroethylene liner of a 50 mL stainless steel reactor and add the cleaned nickel foam; Put the inner container into the reactor, tighten the lid, and put it into the air drying oven for reaction; After the reaction is completed, the reactor is taken out and allowed to cool naturally to room temperature, the inner tank is taken out, the reaction product is taken out and ultrasonically treated with water and ethanol respectively, and then dried in a blast drying oven to obtain a Ni BDC sample, and the obtained sample is marked and packaged; S2. Synthesis of Ni BDC@Fe BDC: Measure N,N-dimethylformamide in a measuring cylinder and pour it into a beaker. Use a balance to weigh FeCl3·6H2O and add it to the beaker. Stir and mix thoroughly with a rubber-tipped dropper, and then pour it into the inner tank of the reactor. Take out Ni BDC and put it into a 50mL inner liner and keep a record, while ensuring that Ni BDC is in full contact with the solution. Put the inner liner into the reactor, tighten the lid, and put it into the air drying oven for reaction; After the reaction is completed, the reactor is taken out and allowed to cool naturally to room temperature. The inner tank is taken out, the reaction product is taken out and washed with water and ethanol respectively, and then placed in a forced air drying oven for drying. After drying, the marked package is taken out to obtain a nickel-iron-based MOFs heterostructure catalyst.
2. The method for synthesizing the nickel-iron-based MOFs heterostructure catalyst according to claim 1, characterized in that: In step S1, the ratio of N,N-dimethylformamide to terephthalic acid is 30 mL-32 mL: 240 mg-250 mg.
3. The method for synthesizing the nickel-iron-based MOFs heterostructure catalyst according to claim 1, characterized in that: In step S1, the ratio of the N,N-dimethylformamide, deionized water and ethanol mixed solution is 30 mL-32 mL: 2 mL-3 mL.
4. The method for synthesizing the nickel-iron-based MOFs heterostructure catalyst according to claim 1, characterized in that: In step S1, the ratio of NiCl2·6H2O to terephthalic acid is 350mg-360mg:240mg-250mg.
5. The method for synthesizing the nickel-iron-based MOFs heterostructure catalyst according to claim 1, characterized in that: In step S1, the inner container is placed in a reaction kettle, the lid is tightened, and the reaction is carried out in a forced air drying oven, wherein the reaction temperature is 100° C.-150° C. and the reaction time is 12 h-24 h.
6. The method for synthesizing the nickel-iron-based MOFs heterostructure catalyst according to claim 1, characterized in that: In step S1, the Ni BDC sample is obtained by drying in a blast drying oven, wherein the drying temperature is 60° C.-80° C.
7. The method for synthesizing the nickel-iron-based MOFs heterostructure catalyst according to claim 1, characterized in that: In step S2, the inner container is placed in a reaction kettle, the lid is tightened, and the reaction is carried out in a forced air drying oven, wherein the reaction temperature is 100° C.-150° C. and the reaction time is 12 h-24 h.
8. The method for synthesizing the nickel-iron-based MOFs heterostructure catalyst according to claim 1, characterized in that: In step S2, a balance is used to weigh the mass of FeCl3·6H2O to be 20 mg to 100 mg.
9. A nickel-iron-based MOFs heterostructure catalyst, characterized in that: The nickel-iron-based MOFs heterostructure catalyst is prepared using the synthesis method described in any one of claims 1 to 8.
10. An application of a nickel-iron-based MOFs heterostructure catalyst, characterized in that: The nickel-iron-based MOFs heterostructure catalyst prepared by the synthesis method according to any one of claims 1 to 8 is applied to electrocatalytic water splitting.